2021
DOI: 10.1016/j.mad.2020.111393
|View full text |Cite
|
Sign up to set email alerts
|

The use of Motor and Cognitive Dual-Task quantitative assessment on subjects with mild cognitive impairment: A systematic review

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…A total of 155 (62%) cases TUG manual; 23 (9.2%) had cognitive and 72 (28.2%) physical problems while performing tasks. The median score was 16 (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) seconds, stride number during the test-23 (19)(20)(21)(22)(23)(24)(25)(26)(27)(28), and while turning around-6 (5)(6)(7)(8). DTC was 11 (0-25)%.…”
Section: Single Task and Dual-task Gait Test Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 155 (62%) cases TUG manual; 23 (9.2%) had cognitive and 72 (28.2%) physical problems while performing tasks. The median score was 16 (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) seconds, stride number during the test-23 (19)(20)(21)(22)(23)(24)(25)(26)(27)(28), and while turning around-6 (5)(6)(7)(8). DTC was 11 (0-25)%.…”
Section: Single Task and Dual-task Gait Test Resultsmentioning
confidence: 99%
“…In recent years an increasing interest in dual-task interference has been evaluated. In a systematic review provided by Mancioppi G et al, 1939 records were identified through database searching years 2010-2020, with 347 full-text articles and 38 studies included in the meta-analysis [19]. The use of single and dual gait speeds was recommended in Canadian guidelines on non-cognitive markers of dementia [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this, dual-task performance depends on mobility, cognitive function and the interplay between cognition and motor control [ 59 ]. The cognitive dual-task testing paradigm was thus considered as a valuable tool for the early detection of mobility and cognitive decline [ 17 , 60 ]. In this study, although no between-group statistical differences were found in 8UG CT and DTC CT , the MCI group tended to have a longer 8UG time and higher DTC value under CT than ST.…”
Section: Discussionmentioning
confidence: 99%
“…The activities of daily life usually involve simultaneous cognitive and motor performance or dual-tasking. Such activities like walking while talking and avoiding obstacles or making turns, become challenging with advancing age ( Mancioppi et al, 2020 ). Dual-task performance can predict the deterioration of gait and cognitive decline in people with neurological deficits.…”
Section: Introductionmentioning
confidence: 99%